Tribological Behavior of Particles and Fiber-Reinforced Hybrid Nanocomposites - Mohanty A.; Srivastava V.K. (My University, 2025)
This article discusses the mechanical performance of alumina nanoparticles and randomly distributed short glass/carbon fiber-reinforced hybrid composites through microhardness and wear test. The open mold casting method was adapted to prepare the test coupons. The wear and friction behavior of composites sliding against hardened ground EN 32 steel in a pin-on-disc configuration is evaluated on a wear and friction tester. The microhardness properties of the neat epoxy, alumina nanoparticles, and alumina nanoparticle–embedded glass/carbon fiber–reinforced hybrid composites were determined. The morphology of the worn composites was analyzed with a scanning electron microscope. It was found that the particles as fillers contributed significantly to improve the mechanical properties and wear resistance of the polymer composites. This is because the fillers contributed to enhance the bonding strength between the fiber and the epoxy resin. Moreover, the wear and friction resistance of the glass/carbon fiber composites was increased by increasing the filler weight in the composite materials. © 2015, Copyright © Society of Tribologists and Lubrication Engineers.